Editorial: Perspectives and Theories of Social Innovation for Ageing Population - Andrzej Klimczuk; Łukasz Tomczyk (Frontiers in Sociology, 2020)
Gerontology together with its subfields, such as social gerontology (sociology of ageing), geragogy, educational gerontology, political gerontology, environmental gerontology, and financial gerontology, is still a relatively new academic discipline that is currently intensively developing, expanding research fields and combining various theoretical and practical perspectives. The interdisciplinarity, transdisciplinarity, and multidisciplinarity of research on ageing and old age, despite its vast thematic, methodological and theoretical diversity, have a common denominator, which is the focus of research work on improving the quality of life of older people (see Fabiś et al., 2015). It is the concern for the components of quality of life such as welfare and well-being as well as focus on learning about phenomena conditioning successful ageing that has become motivators and premises hidden or visible in many texts included in the Research Topic "Perspectives and Theories of Social Innovation for Ageing Population." The Research Topic that we are presenting to our readers is unique not only because of its size but above all because of its novelty and social involvement, visible in the content of individual chapters. The presented collection includes 17 articles prepared in total by 76 authors from the following countries: China, Finland, Germany, Ghana, Hungary, Ireland, Israel, Italy, Japan, the Netherlands, Poland, Portugal, Slovenia, Spain, Sweden, the United Kingdom, and the United States. Two journals were combined with this Research Topic: "Frontiers in Public Health" and "Frontiers in Sociology." The presented Research Topic contains seven types of articles covering: two community case studies (Brown et al.; Pinzón-Pulido et al.), eight original research articles (Berde; Bjursell; Dovie; Senior; Spinelli et al.; Stypińska et al.; Wanka; Zhang and Yang), two perspective articles (Aoo et al.; Piel and Robra), one hypothesis and theory paper (Toczyski et al.), one policy and practice review (Tziraki-Segal et al.), one methods article (Ramovš et al.), and two book reviews (Cieśla; Leszko).
Keywords: J14; J18; 330; ageing; social gerontology; social innovation; caregivers; age-friendly; public health; healthcare